Mechanisms for promoting audiovisual works on foreign OTT services - A. R. Akopyan; A. M. Arakelyan; Yu. V. Vorontsova; V. V. Krysov (Вестник университета)
Recently, there has been an increase in the number of companies seeking to create digital platforms. Developing and investing in their own original content has opened up the opportunity for Russian services and companies to promote it on foreign platforms, gaining access to new markets and increasing attractiveness for potential foreign investors. The cultural content transmission works on the principle of streaming, which continuously delivers individualised information to the user via the Internet. Domestic OTT services, unlike TV channels, have not yet decided on their positioning. Platforms do not focus on individual segments, but on a variety of content that has a potential viewer. This strategy is aimed at attracting the maximum number of new subscribers. The emergence of streaming services has brought with it new opportunities for producers from various countries. In order to effectively promote audiovisual content, the authors justified and selected criteria for conducting a comparative analysis of mechanisms for promoting audiovisual works on foreign OTT services so that the company could choose the most appropriate one for itself.